Systematic Literature Review on Optical Character Recognition Methods for Text Extraction - Nurcahyo, Krisna Bayu Aditya; Ricky Eka Putra; Yuni Yamasari (Jurnal Serambi Engineering, 2026)
The development of technology has driven a significant increase in the need for document digitization and automation of text-based data processing. A systematic review is needed to identify progress related to the development of OCR in text extraction. Therefore, this study presents a systematic literature review on the development and use of OCR in text extraction using the PRISMA method. The study began with an initial search of 38 studies, which were then selected based on established criteria. Seven relevant articles were successfully identified through a focused search using the keywords "Optical Character Recognition/OCR." The results of the literature review analysis show that the Convolutional Neural Network (CNN) method is the most widely used approach in the development of OCR for text extraction. In addition, the analysis results also reveal that OCR has been applied in various fields, including healthcare, public administration, government, transportation, and commercial services. This study also highlights the various benefits as well as several challenges that are still faced in the future development of OCR. These challenges include improving character recognition accuracy and handling font variations as well as image quality. Thus, the insights generated by this research contribute to the development of OCR as a more reliable and effective tool in supporting document digitization processes.